Advantage of the subcutaneous immunoglobulin replacement therapy in primary immunodeficient patients with or without secondary protein loss - Pınar Gür-Çetinkaya; Deniz Nazire Çağdaş-Ayvaz; Ayça Burcu Öksüz; Ayşe Ertoy; Umut Hayran; Feride Özkan; Meliha Erol; İlhan Tezcan (The Turkish Journal of Pediatrics)
In recent years subcutaneous immunoglobulin is widely used for primary immunodeficient patients. Subcutaneous administration provides a more stable and higher serum immunoglobulin levels due to continuous and steady transition from lymphatics to the systemic circulation. We aimed to evaluate the changes in serum immunoglobulin levels under subcutaneous immunoglobulin therapy in patients with primary immunodeficiency with or without secondary protein loss. Nine patients with primary immunodeficiency who switched to subcutaneous immunoglobulin were enrolled. Age, gender, diagnosis, reasons of transition to subcutaneous route, reasons of secondary protein loss were recorded. A questionnaire consisting of frequencies and types of infections, side effects observed with intravenous and subcutaneous routes; date and reason of transition to subcutaneous route were asked to all participants. Serum immunoglobulin levels at the 3rd and the 6th months before and after subcutaneous route were recorded. Of the 9 patients (M/F=4/5) the median age was 12 years (6.1-28.7) and 5 of them had protein loss. In total, 444 injections were applied, and all patients experienced local reactions. Infections were more frequent under intravenous than subcutaneous route (p=0.004). We observed an increase in immunoglobulin levels under subcutaneous route (p=0.069 at 3rd; p=0.13 at 6th month). This increase was evident at the 3rd month of transition to subcutaneous route in patients with protein loss (p=0.080). There was an increase in serum immunoglobulin levels under subcutaneous route. However, increase was not statistically significant since the study group was small. This increment was prominent in patients with protein loss. Subcutaneous administration may be a good alternative for primary immunodeficient patients with protein loss who have persistent low serum immunoglobulin levels despite increments in the intravenous immunoglobulin doses.